Negative pole piece, preparation method thereof, lithium battery without negative pole and lithium battery
By using a lithium-philic active layer composed of nanowires and conductive particles in the negative electrode sheet of the lithium battery, the problems of improving the energy density and cycling stability of the lithium battery are solved, and higher Coulomb efficiency and cycling performance are achieved.
Patent Information
- Application Number
- CN202411966589.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-05-02
AI Technical Summary
The specific capacity of graphite or silicon-doped negative electrode used in existing lithium-ion batteries is low, which limits the further improvement of its energy density. In addition, metal lithium negative electrodes have dendrite problems, side reactions and volume expansion effects, affecting Coulomb efficiency and cyclic stability.
A negative electrode sheet is proposed, including a current collector and a lithium-philic active layer. The lithium-philic active layer is composed of nanowires and conductive particles dispersed on the nanowires. The nanowires provide nucleation sites for lithium metals and reduce the production of lithium dendrites.
It improves the Coulomb efficiency and cyclic stability of lithium batteries, reduces the production of lithium dendrites, and improves the cyclic performance and energy density of the battery.
Smart Images

Figure CN119920826A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a negative electrode plate and a preparation method thereof, a negative electrode-free lithium battery and a lithium battery. Background Art
[0002] Lithium-ion batteries have become the first choice for consumer electronic batteries and new energy vehicle power batteries due to their advantages such as high energy density, long cycle life and no memory effect. However, the graphite or silicon-doped negative electrodes used in existing lithium-ion batteries have low specific capacity, which limits the further improvement of their energy density.
[0003] The metallic lithium negative electrode has a specific capacity of 3860mAh / g. Its use will greatly improve the energy density of lithium batteries. However, the dendrite problem, side reaction problem with the electrolyte and volume expansion effect of the metallic lithium negative electrode will affect the coulombic efficiency and cycle stability of the lithium battery, limiting the commercial application of the metallic lithium negative electrode. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, one object of the present invention is to provide a negative electrode plate and a preparation method thereof, a negative electrode-free lithium battery and a lithium battery. The negative electrode plate provided in the present application can improve the coulombic efficiency and cycle stability of the battery.
[0005] In the first aspect of the present invention, the present invention proposes a negative electrode plate. According to an embodiment of the present invention, the negative electrode plate includes: a current collector and a lithium-philic active layer, the lithium-philic active layer is arranged on at least one side of the current collector, the lithium-philic active layer includes nanowires and conductive particles dispersed on the nanowires, and when lithium metal is deposited, the nanowires provide nucleation sites for the lithium metal.
[0006] According to the negative electrode sheet of the above embodiment of the present invention, the current collector serves as a basic support, the lithium-philic active layer is arranged on at least one side of the current collector, and the nanowires can serve as the substrate of the lithium-philic active layer, providing a homogeneous high-speed channel and providing a monodisperse active attachment site for the composite of the conductive particles, solving the problems of too low specific surface area of single active site particles and easy agglomeration, and the one-dimensional nanowires can further reduce the contact area with the battery electrolyte, reduce the side reactions of the system, and improve the cycle performance of the battery containing them; the integrated composite negative electrode composed of silver nanowires and conductive particles can simultaneously realize the stable transmission channel at the atomic level of the bulk phase and the interface , which eliminates the problem of disordered growth of lithium dendrites caused by uneven dispersion of nanowires and conductive particles from the source, and improves the cycle performance and coulombic efficiency of the battery; in addition, the position where the conductive particles contact the nanowires is constructed as a homogeneous interface and a highly active lithium conductive site, which can effectively increase the content of effective active sites per unit area, improve the cycle performance and coulombic efficiency of the battery, and can also reduce the amount of raw materials used and reduce the cost of battery use. In summary, the negative electrode plate proposed in the present application is conducive to the uniform deposition of lithium metal during the battery charging process, and can reduce lithium dendrites and improve the cycle performance and coulombic efficiency of the battery.
[0007] In addition, the negative electrode sheet according to the above embodiment of the present invention may also have the following additional technical features:
[0008] In some embodiments of the present invention, the diameter of the nanowire is 1 nm-100 nm, preferably 2 nm-100 nm, thereby improving the coulombic efficiency and cycle stability of the lithium battery.
[0009] In some embodiments of the present invention, the length of the nanowire is 500 nm-100 μm, preferably 1 μm-80 μm, thereby improving the cycle performance and coulombic efficiency of the lithium battery.
[0010] In some embodiments of the present invention, the nanowire includes a first nanowire and a second nanowire, the first nanowire has a length of 10 μm-100 μm, and the second nanowire has a length of 1 μm-20 μm. Thus, the cycle performance and coulombic efficiency of the lithium battery can be improved.
[0011] In some embodiments of the present invention, the Dv50 particle size of the conductive particles is 0.5 nm-100 nm, thereby improving the coulombic efficiency and cycle performance of the lithium battery.
[0012] In some embodiments of the present invention, the compaction density of the lithium-philic active layer is 0.3 g / cm 3 -2.0g / cm 3 . Thereby, the coulombic efficiency and cycle performance of the lithium battery can be improved.
[0013] In some embodiments of the present invention, the mass ratio of the nanowires to the conductive particles is (1:9)-(9:1). Thus, the coulombic efficiency and cycle performance of the lithium battery can be improved.
[0014] In some embodiments of the present invention, the nanowires include at least one of solid electrolyte nanowires, silver nanowires, magnesium nanowires, zinc nanowires, nickel nanowires, aluminum nanowires, gold nanowires, molybdenum nanowires, lead nanowires, tin nanowires, bismuth nanowires, palladium nanowires, ruthenium nanowires, iridium nanowires, platinum nanowires, cerium nanowires, indium nanowires, silicon nanowires and their oxide nanowires, sulfide nanowires, and solid electrolyte nanowires. Thus, the cycle stability and coulombic efficiency of lithium batteries are improved.
[0015] In some embodiments of the present invention, the conductive particles include at least one of one-dimensional conductive particles, two-dimensional conductive particles, and three-dimensional conductive particles, thereby improving the coulombic efficiency and cycle performance of the lithium battery.
[0016] In some embodiments of the present invention, the conductive particles include at least one of carbon quantum dots, fullerenes, conductive carbon black, conductive graphite, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, graphene, silicon carbide, boron carbide, silicon boride, vanadium boride, magnesium boride, and titanium boride. Thus, the coulombic efficiency and cycle performance of the lithium battery can be improved.
[0017] In some embodiments of the present invention, the nanowires are grafted with functional groups, which include at least one of silicon-containing functional groups, nitrogen-containing functional groups, sulfur-containing functional groups and boron-containing functional groups, thereby improving the coulombic efficiency and cycle performance of the lithium battery.
[0018] In some embodiments of the present invention, the conductive particles further include a blend, wherein the blend includes at least one of a solid electrolyte and a conductive polymer, thereby improving the coulombic efficiency and cycle performance of the lithium battery.
[0019] In some embodiments of the present invention, the mass proportion of the blend is 0.1%-10% based on the total mass of the conductive particles, thereby improving the cycle life and coulombic efficiency of the battery.
[0020] In some embodiments of the present invention, the conductive polymer comprises a nitrogen-containing polymer.
[0021] In some embodiments of the present invention, the conductive polymer includes at least one of polyaniline, polythiophene, polyphenylene sulfone resin, polyurethane, polyamide, 6-amino-1-hexanol-polyacrylic acid ion cross-linked polymer, hydroxyethylethylenediamine-polyacrylic acid ion cross-linked polymer, diglycolamine-polyacrylic acid ion cross-linked polymer, 5-amino-1-pentanol-polyacrylic acid ion cross-linked polymer, 4-amino-1-butanol-polyacrylic acid ion cross-linked polymer, and N,N-bis(2-hydroxyethyl)ethylenediamine-polyacrylic acid ion cross-linked polymer.
[0022] In some embodiments of the present invention, the thickness of the lithium-philic active layer is 10 μm-200 μm, preferably 30 μm-120 μm, thereby improving the cycle performance and coulombic efficiency of the battery.
[0023] In some embodiments of the present invention, the mass of the functional groups accounts for 0.1%-3% of the mass of the nanowires, thereby improving the cycle performance and rate performance of the battery.
[0024] In some embodiments of the present invention, the lithium-philic active layer further comprises a binder and an active additive, thereby improving the cycle performance and rate performance of the battery.
[0025] In some embodiments of the present invention, based on the total mass of the lithium-philic active layer, the mass proportion of the binder is less than or equal to 3%, thereby improving the cycle performance and coulombic efficiency of the battery.
[0026] In some embodiments of the present invention, based on the total mass of the lithium-philic active layer, the mass proportion of the active additive is 0.1%-10%, thereby improving the cycle performance and rate performance of the battery.
[0027] In some embodiments of the present invention, the binder includes at least one of polyvinylidene fluoride, polyvinyl alcohol, polytetrafluoroethylene, sodium hydroxymethyl cellulose, styrene-butadiene rubber, nitrile rubber, styrene-butadiene-styrene copolymer, polyacrylic acid, and lithium polyacrylate, thereby improving the cycle performance and rate performance of the battery.
[0028] In some embodiments of the present invention, the active additive includes at least one of lithium nitrate, lithium fluoride, and lithium nitride, thereby improving the cycle performance and rate performance of the battery.
[0029] In a second aspect of the present invention, the present invention proposes a method for preparing the above-mentioned negative electrode sheet. According to an embodiment of the present invention, the method comprises: preparing a lithium-philic active layer on at least one side of a current collector, the lithium-philic active layer comprising nanowires and conductive particles dispersed on the nanowires, and when lithium metal is deposited, the nanowires provide nucleation sites for the lithium metal. Thus, the coulombic efficiency and cycle performance of the battery can be improved.
[0030] In some embodiments of the present invention, the lithium-philic active layer is prepared by the following method:
[0031] The nanowires dispersed with conductive particles, a binder and an active additive are dispersed in an organic solvent to obtain a slurry, which is then coated on a current collector and dried to obtain a negative electrode sheet, thereby improving the coulombic efficiency and cycle stability of the lithium battery.
[0032] In some embodiments of the present invention, the nanowires include silver nanowires, the silver nanowires are grafted with functional groups, the functional groups include at least one of silicon-containing functional groups, nitrogen-containing functional groups, sulfur-containing functional groups and boron-containing functional groups, and the silver nanowires are prepared by the following method: a silver nanowire precursor, a functional group precursor, a reducing agent, a surfactant and a solvent are mixed, and a reduction reaction is performed to obtain silver nanowires grafted with functional groups. Thus, the coulombic efficiency and cycle stability of the lithium battery can be improved.
[0033] In some embodiments of the present invention, the functional group precursor includes at least one of dopamine, silicon fluoride, aromatic amine, sulfonylated amine, halogenated aromatic amine, nitrogen-containing heterocyclic compounds, nitrile compounds, nitro compounds, thiophenyl compounds, furanyl thiocarboxylates and thiourea, thereby improving the rate performance and cycle stability of the lithium battery.
[0034] In some embodiments of the present invention, the temperature of the reduction reaction is 60° C.-180° C., thereby being able to improve the coulombic efficiency and cycle stability of the lithium battery.
[0035] In some embodiments of the present invention, the silver nanowire precursor includes a silver salt, and the silver salt includes at least one of silver nitrate, silver bromide, silver sulfate, silver fluoride, silver perchlorate, and silver acetate, thereby improving the rate performance and cycle stability of the lithium battery.
[0036] In some embodiments of the present invention, the surfactant includes cupric chloride, cuprous chloride, sodium chloride, cupric bromide, cuprous bromide, ferric chloride, ferrous chloride, ferric bromide, ferrous bromide, trioctyl phosphine, trioctyl phosphine oxide, long chain alkyl salt, polyvinyl pyrrolidone, oleylamine, polyethylene glycol, tween, triethanolamine, hexadecyl trimethyl ammonium bromide, polyacrylamide, di-(2-ethylhexyl) sodium sulfosuccinate, sodium dodecyl sulfate, lithium dodecyl sulfate, dodecyl dimethyl ammonium chloride, dodecyl trimethyl ammonium chloride, dodecyl dimethyl benzyl ammonium chloride, dodecyl dimethyl ammonium oxide, dodecyl betaine, hexadecyl trimethyl ammonium chloride, and at least one of amidopropyl betaine. Thus, the rate performance and cycle stability of the lithium battery can be improved.
[0037] In some embodiments of the present invention, the nanowires dispersed with conductive particles are prepared by the following method: dispersing the conductive particles in a first solvent to prepare a first suspension; dispersing the nanowires in a second solvent to prepare a second suspension; mixing the first suspension and the second suspension, and drying to obtain nanowires dispersed with conductive particles. Thus, the rate performance and cycle stability of the lithium battery can be improved.
[0038] In the third aspect of the present invention, the present invention provides a negative electrode-free lithium battery. According to an embodiment of the present invention, the diaphragm-free lithium battery comprises the negative electrode plate of the first aspect or the negative electrode plate prepared by the method of the second aspect. The negative electrode-free lithium battery has excellent cycle performance and coulombic efficiency.
[0039] In a fourth aspect of the present invention, the present invention provides a lithium battery. According to an embodiment of the present invention, the lithium battery comprises the negative electrode sheet of the first aspect or the negative electrode sheet prepared by the method of the second aspect. The lithium battery has excellent cycle performance and coulombic efficiency.
[0040] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0042] Figure 1 A schematic structural diagram of a negative electrode sheet according to an embodiment of the present invention is shown.
[0043] Figure 2 A schematic diagram of the magnified structure of the lithiophilic active layer is shown.
[0044] Figure Number:
[0045] Negative electrode sheet 10, current collector 1, lithium-philic active layer 2, nanowires 21, and conductive particles 22. DETAILED DESCRIPTION
[0046] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0047] In the first aspect of the present invention, the present invention provides a negative electrode sheet 10. According to an embodiment of the present invention, referring to Figure 1 The negative electrode plate 10 includes a current collector 1 and a lithium-philic active layer 2 .
[0048] The current collector 1 plays an important role in basic support, electron transport and fixation of the lithium-philic active layer 2 in the negative electrode plate 10, and is a key component to ensure battery performance and stability. There is no special limitation on the type of the current collector 1, and those skilled in the art can select it as needed.
[0049] As an example, the current collector 1 includes but is not limited to at least one of copper foil, aluminum foil, stainless steel and a composite current collector 1 .
[0050] As an example, the composite current collector 1 includes an organic material substrate and an inorganic metal layer on the surface of the substrate, wherein the organic material substrate includes but is not limited to at least one of polyethylene terephthalate, polybutylene terephthalate, polystyrene and polypropylene, and the material of the inorganic metal layer on the surface includes but is not limited to at least one of aluminum, aluminum alloy, copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, gold and gold alloy.
[0051] According to an embodiment of the present invention, the lithium-philic active layer 2 is disposed on at least one side of the current collector 1, and the lithium-philic active layer 2 includes nanowires 21 and conductive particles 22 dispersed on the nanowires 21. When lithium metal is deposited, the nanowires 21 provide nucleation sites for the lithium metal.
[0052] According to the negative electrode sheet 10 of the above embodiment of the present invention, the current collector 1 serves as a basic support, and the lithium-philic active layer 2 is arranged on at least one side of the current collector 1. When the battery is charged, the nanowires 21 provide nucleation sites for lithium metal, can serve as the substrate of the lithium-philic active layer 2, provide a homogeneous high-speed channel, and provide a monodisperse active attachment site for the composite of the conductive particles 22, thereby solving the problems of low specific surface area of particles at a single active site and easy agglomeration, and the one-dimensional nanowires 21 can further reduce the contact area with the battery electrolyte, reduce the side reactions of the system, and improve the cycle performance of the battery containing it; the integrated composite negative electrode composed of the silver nanowires and the conductive particles 22 can simultaneously realize the stable transmission of the bulk phase and the interface at the atomic level. The problem of disordered growth of lithium dendrites caused by uneven dispersion of nanowires 21 and conductive particles 22 is eliminated from the source, and the volume expansion of the negative electrode during the charging and discharging process can be suppressed, thereby improving the cycle performance and coulombic efficiency of the battery; in addition, the position where the conductive particles 22 contact the nanowires 21 is constructed as a homogeneous interface and a highly active lithium conductive site, which can effectively increase the content of effective active sites per unit area, improve the cycle performance and coulombic efficiency of the battery, and can also reduce the amount of raw materials used and reduce the cost of battery use. In summary, the negative electrode plate 10 proposed in the present application is conducive to the uniform deposition of lithium metal during the battery charging process, and can reduce lithium dendrites and improve the cycle performance and coulombic efficiency of the battery.
[0053] It can be understood that the nanowire 21 refers to a linear material, and the diameter of the cross section of the nanowire 21 is at the nanometer level.
[0054] According to some embodiments of the present invention, the diameter of the nanowire 21 is 1nm-100nm. For example, it can be 1nm, 10nm, 30nm, 50nm, 70nm, 90nm, 100nm, etc. The diameter of the nanowire 21 refers to the diameter of the cross section of the nanowire 21. By controlling the diameter of the nanowire 21 within the above range, it is convenient for the deposition of lithium metal, and it is convenient for the conductive particles 22 to be uniformly deposited thereon, reducing the agglomeration of the nanowire 21 and the conductive particles 22, further improving the lithium conductivity and electrical conductivity of the lithium-philic active layer 2, reducing the generation of lithium dendrites, and improving the coulombic efficiency and cycle stability of the lithium battery. According to some other embodiments of the present invention, the diameter of the nanowire 21 is 2nm-100nm.
[0055] According to some embodiments of the present invention, the length of the nanowire 21 is 1 μm-100 μm. For example, it can be 1 μm, 10 μm, 20 μm, 50 μm, 80 μm, 100 μm, etc. By controlling the length of the nanowire 21 within the above range, it is convenient to obtain the required thickness of the lithium-philic active layer 2 when preparing the negative electrode plate 10, reduce the agglomeration of the conductive particles 22 and the nanowires 21, further improve the lithium conductivity and electrical conductivity of the lithium-philic active layer 2, promote the uniform deposition of lithium metal, further improve the lithium conductivity and electrical conductivity of the lithium-philic active layer 2, reduce the generation of lithium dendrites, and improve the coulombic efficiency and cycle stability of the lithium battery. According to other embodiments of the present invention, the length of the nanowire 21 is 1 μm-80 μm.
[0056] It can be understood that the diameter and length of the nanowire 21 mentioned above refer to the average diameter and average length of the nanowire 21 respectively.
[0057] According to some embodiments of the present invention, the nanowire 21 includes a first nanowire and a second nanowire, the length of the first nanowire is 10μm-100μm, and the length of the second nanowire is 1μm-20μm. As an example, the length of the first nanowire can be 10μm-90μm, 20μm-70μm, 30μm-60μm, 40μm-50μm, etc., and the length of the second nanowire can be 1μm-19μm, 5μm-15μm, 10μm-14μm, etc. Therefore, when two lengths of nanowires 21 are used, when the lithium-philic active layer 2 is prepared, the short nanowires 21 can be filled into the gaps between the long nanowires 21, thereby improving the compaction density of the lithium-philic active layer, and then when the battery is charged, the deposition of lithium metal is made more compact, thereby improving the energy density of the battery.
[0058] According to some embodiments of the present invention, the compaction density of the lithium-philic active layer 2 is 0.3 g / cm3 -2.0g / cm 3 , for example, it can be 0.3 g / cm 3 -1.9g / cm 3 , 0.5g / cm 3 -1.5g / cm 3 , 0.8g / cm 3 -1g / cm 3 Etc., control the compaction density within the above range, so that the deposition of lithium metal is more compact when the battery is charged, thereby improving the energy density of the battery.
[0059] According to some embodiments of the present invention, the Dv50 particle size of the conductive particles 22 is 0.5nm-100nm. For example, it can be 0.5nm, 10nm, 30nm, 50nm, 80nm, 100nm, etc. Limiting the Dv50 particle size of the conductive particles 22 within the above range is conducive to the uniform dispersion of the conductive particles 22 on the nanowires 21. The positions where the conductive particles 22 contact the nanowires 21 are constructed as homogeneous interfaces and highly active lithium-conducting conductive sites, which can effectively increase the content of effective active sites per unit area, facilitate the deposition of lithium metal, and facilitate the uniform deposition of the conductive particles 22 thereon, reduce the agglomeration of the nanowires 21 and the conductive particles 22, further improve the lithium-conducting and conductive properties of the lithium-philic active layer 2, reduce the generation of lithium dendrites, and improve the coulombic efficiency and cycle performance of the lithium battery.
[0060] It should be noted that the Dv50 particle size refers to the particle size corresponding to when the cumulative volume distribution percentage reaches 50%, and is measured using a laser particle size analyzer (eg, Malvern Master Size 3000) with reference to the standard GB / T 19077-2016.
[0061] According to some embodiments of the present invention, the mass ratio of the nanowire 21 to the conductive particles 22 is (1:9)-(9:1). For example, it can be 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, etc. By controlling the mass ratio of the nanowire 21 to the conductive particles 22 within the above range, the lithium conductivity of the lithium-philic active layer 2 can be taken into account, and the nanowire 21 and the conductive particles 22 can be dispersed more evenly, further improving the uniform deposition of lithium metal, reducing the generation of lithium dendrites, and improving the coulombic efficiency and cycle stability of lithium batteries, especially negative electrode-free lithium batteries.
[0062] According to some embodiments of the present invention, the nanowire 21 includes at least one of silver nanowire, magnesium nanowire, zinc nanowire, nickel nanowire, aluminum nanowire, gold nanowire, molybdenum nanowire, lead nanowire, tin nanowire, bismuth nanowire, palladium nanowire, ruthenium nanowire, iridium nanowire, platinum nanowire, cerium nanowire, indium nanowire, silicon nanowire and oxides or sulfides of the above nanowires, and solid electrolyte nanowires. The above nanowire 21 can form an alloy when reacting with lithium, has good lithium affinity, makes it easier for lithium ions to be adsorbed and desorbed on the surface of the negative electrode plate 10, reduces the polarization degree of the battery, helps to improve the charge and discharge efficiency of the battery, reduces energy loss, and can improve the cycle performance of the lithium battery.
[0063] It is understandable that the above-mentioned types of nanowires 21 can be purchased on the market, or can be prepared using the nanowire 21 preparation methods commonly used in the art (such as reduction method, electrostatic spinning method, etc.).
[0064] According to some embodiments of the present invention, the conductive particles 22 include at least one of one-dimensional conductive particles 22, two-dimensional conductive particles 22, and three-dimensional conductive particles 22. The conductive particles 22 of the above morphology have good conductivity and can be evenly dispersed on the nanowires 21. The positions where the conductive particles 22 contact the nanowires 21 are constructed as homogeneous interfaces and highly active lithium-conducting conductive sites, which can effectively increase the content of effective active sites per unit area and improve the cycle performance and coulombic efficiency of the battery.
[0065] According to some embodiments of the present invention, the conductive particles 22 include at least one of carbon quantum dots, fullerenes, conductive carbon black, conductive graphite, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, graphene, silicon carbide, boron carbide, silicon boride, vanadium boride, magnesium boride, and titanium boride. The conductive particles 22 of the above morphology have good conductivity and can be evenly dispersed on the nanowires 21. The positions where the conductive particles 22 contact the nanowires 21 are constructed as homogeneous interfaces and highly active lithium conductive sites, which can effectively increase the content of effective active sites per unit area, facilitate the rapid transmission of electrons in the negative electrode sheet 10, reduce the internal resistance of the battery, and improve the cycle performance and coulomb efficiency of the battery.
[0066] According to some embodiments of the present invention, functional groups are grafted onto the nanowires 21, and the functional groups include at least one of silicon-containing functional groups, nitrogen-containing functional groups, sulfur-containing functional groups and boron-containing functional groups. At least one of the silicon-containing functional groups, nitrogen-containing functional groups, sulfur-containing functional groups and boron-containing functional groups can be stably grafted onto the lithium-philic active sites. The grafting of functional groups can effectively prevent the agglomeration of the lithium-philic active sites, ensure that the lithium-philic active sites can be evenly distributed on the current collector 1 in a dispersed state, and then induce the lithium metal to be evenly dispersed on the current collector 1; the grafting of functional groups can also firmly anchor the lithium-philic active sites on the surface of the current collector 1, prevent the lithium-philic active sites from falling off or moving during the battery cycle, which is beneficial to maintaining the battery's cycle stability; the lithium-philic active sites grafted with functional groups can form lithium metal nucleation sites, inducing lithium ions to be directional deposited along the (110) crystal plane, thereby inhibiting the disordered growth of lithium dendrites, which is beneficial to improving the safety performance and cycle stability of lithium batteries.
[0067] It can be understood that when functional groups are grafted onto the nanowire 21, the mass of the functional groups is also included in the nanowire 21. As an example, when the mass ratio of the nanowire 21 to the conductive particles 22 is defined, the mass of the nanowire 21 includes the mass of the nanowire 21 itself (such as silver nanowire) and the mass of the functional groups.
[0068] According to some embodiments of the present invention, the mass of the functional group accounts for 0.1%-3% of the mass of the nanowire 21. For example, it can be 0.1%, 1%, 2%, 3%, etc. Controlling the mass proportion of the functional group within the above range can further maintain the dispersed state of the lithium-philic active sites, effectively prevent the agglomeration of the lithium-philic active sites, improve the stability and reliability of the negative electrode sheet 10, and thus enhance the cycle performance of the lithium battery; the grafting of the functional group can induce the uniform deposition of lithium ions, inhibit the growth of lithium dendrites, and help improve the safety performance of the lithium battery.
[0069] According to some embodiments of the present invention, the conductive particles 22 also include a blend, which includes at least one of a solid electrolyte and a conductive polymer. On the one hand, the conductive particles 22 are easy to agglomerate. The presence of the blend can reduce the probability of agglomeration of the conductive particles 22 and improve the dispersibility of the conductive particles 22. On the other hand, after the above-mentioned blend is combined with the conductive particles 22 (carbon quantum dots, fullerenes, conductive carbon black, etc.) and evenly dispersed on the nanowires 21, during the battery charging and discharging process, the electric field around the conductive particles 22 is more uniform, so that the deposition of lithium metal at the contact position between the conductive particles 22 and the nanowires 21 is also more uniform, thereby inhibiting the growth of lithium dendrites and improving the battery's cycle performance and coulomb efficiency.
[0070] In addition, the combination of the blend and conductive particles 22 (carbon quantum dots, fullerenes, conductive carbon black, etc.) can effectively inhibit the growth and volume expansion of lithium dendrites, form an integrated stable SEI, and solve the problem of micro-short circuits in the battery during charging and discharging. The uniform mixing of the blend and highly dispersed nanowires 21 reduces its contact area with the electrolyte, reduces side reactions with the electrolyte, and can improve the cycle stability of the battery.
[0071] According to some embodiments of the present invention, based on the total mass of the conductive particles 22, the mass proportion of the blend is 0.1%-10%, for example, it can be 0.1%, 1%, 3%, 5%, 8%, 10%, etc., and controlling the mass proportion of the blend within the above range can further reduce the risk of agglomeration of the conductive particles 22, making the electric field around the conductive particles 22 more uniform, and making the deposition of lithium metal at the contact position between the conductive particles 22 and the nanowires 21 more uniform, thereby inhibiting the growth of lithium dendrites and improving the cycle performance and coulombic efficiency of the battery.
[0072] According to some embodiments of the present invention, the conductive polymer includes a nitrogen-containing polymer, specifically, the nitrogen-containing polymer includes at least one of polyaniline, polythiophene, polypyrrole, polyphenylene sulfone resin, polyurethane, polyamide, 6-amino-1-hexanol-polyacrylic acid ion cross-linked polymer, hydroxyethylethylenediamine-polyacrylic acid ion cross-linked polymer, diglycolamine-polyacrylic acid ion cross-linked polymer, 5-amino-1-pentanol-polyacrylic acid ion cross-linked polymer, 4-amino-1-butanol-polyacrylic acid ion cross-linked polymer, and N,N-bis(2-hydroxyethyl)ethylenediamine-polyacrylic acid ion cross-linked polymer. The above-mentioned nitrogen-containing polymer can further reduce the risk of agglomeration of the conductive particles 22, make the electric field around the conductive particles 22 more uniform, and make the deposition of lithium metal at the contact position between the conductive particles 22 and the nanowires 21 more uniform, thereby inhibiting the growth of lithium dendrites and improving the cycle performance and coulomb efficiency of the battery.
[0073] It should be noted that there is no particular limitation on the type of solid electrolyte, and those skilled in the art can flexibly select it according to needs.
[0074] As an example, the solid electrolyte includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a hydride solid electrolyte, a borate solid electrolyte, a nitride solid electrolyte and a polymer solid electrolyte.
[0075] As an example, the oxide solid electrolyte includes at least one of a garnet-type solid electrolyte, a perovskite-type solid electrolyte, a NASICON-type solid electrolyte, and a LISICON-type solid electrolyte.
[0076] It should be noted that NASICON-type active fillers refer to active materials with a sodium superionic conductor (Na Super Ionic Conductor, NASICON) structure, which is a three-dimensional open framework structure composed of metal ions and polyhedrons; LISICON-type active fillers refer to a class of materials with a lithium superionic conductor (Lithium Super Ionic Conductor, LISICON) structure.
[0077] As an example, the garnet-type solid electrolyte includes Li x1 LqCy y1 A1 z1 O 12 and Li x2 La 3-y2 B1 y2 Zr z2 O 12 At least one of the following, wherein Li x1 LqCy y1 A1 z1 O 12 Satisfies: 6≤x1≤7, 1≤y1≤2, 0≤z1≤0.5, A1 includes at least one of Ta, Nb, Mg, Ti, Te, W; Li x2 La 3-y2 B1 y2 Zr z2 O 12 Satisfies: 6≤x2≤7, 0≤y2≤0.5, 1≤z2≤2, and B2 includes at least one of Ca, Rb, Al, and Ga.
[0078] As an example, the perovskite solid electrolyte includes Li 3.3 La 0.53 TiO3Li 3x3 La 2 / 3-x3 TiO3, Li 3.3 La 0.53 TiO3Li 3x3 La 2 / 3-x3 TiO3 satisfies: 0≤x3≤2 / 3;
[0079] As an example, the NASICON-type solid electrolyte includes Li x5 Al y4 M2 z4 (PO4)3、Li x6 Y y5 Zr z5 At least one of Li(PO4)3, LiTi2(PO4)3, LiGe2(PO4)3 and LiGeTi(PO4)3, wherein Li x5 Aly4 M2 z4 (PO4)3 satisfies: 1.3≤x5≤1.5, 0.3≤y4≤0.5, 1.5≤z4≤1.7, M2 includes at least one of Ti, Ge, Hf, Zn, Zr and Si; Li x6 Y y5 Zr z5 (PO4)3 satisfies: 1.3≤x6≤1.5, 0.3≤y5≤0.5, 1.5≤z5≤1.7.
[0080] As an example, the LISICON type solid electrolyte includes Li 3+x7 (P 1x7 Si x7 )O4 and Li 3+x8 Ge x8 V 1x8 At least one of O4, wherein Li 3+x7 (P 1x7 Si x7 )O4 satisfies: 0≤x7≤0.5; Li 3+x8 Ge x8 V 1x8 O4 satisfies: 0.25≤x8≤0.72.
[0081] As an example, the sulfide solid electrolyte includes Argyrodite-type LiPSM3X1, Thio-LiSICON-type Li 4-x9 A2 1-x9 B2 x9 S4 and at least one of glassy sulfides, wherein LiPSM3X1 satisfies: M3 includes at least one of O, Cu, Zn, Bi, Sn, Al, Mn, Ce and In, and X1 includes at least one of F, Cl, Br and I; Li 4-x9 A 1-x9 B x9 S4 satisfies: 0≤x9≤0.5, A2 includes at least one of Si, Sn, Ge and Zr, and B2 includes at least one of O, P, Al, Zn and Ga.
[0082] As an example, the glassy sulfide includes at least one of Li2S-P2S5, Li2S-GeS2, Li2S-SiS2, Li2S-SiS2-Li4SiO4, Li2S-B2S3 and Li2S-B2S3-LiI.
[0083] As an example, the halide solid electrolyte includes LiX2, Li2M4X34, Li3M5X46, Li x M6 y Ln zCl3, LiM7Cl5X5, and Li 3-y7 Zr y7 M8 1-y7 At least one of Cl6, where LiX2 satisfies: X2 includes at least one of F, Cl, Br, and I; Li2M4X34 satisfies: M4 includes at least one of Mg, Mn, Fe, Zn, and Cd, and X3 includes at least one of F, Cl, Br, and I; Li3M5X46 satisfies: M5 includes at least one of O, In, Y, Yb, Sc, Ho, and Er, and X4 includes at least one of F, Cl, Br, and I; Li x10 M6 y6 Ln z6 Cl3 satisfies: 0 ≤ x10 ≤ 0.5, 0 ≤ y6 ≤ 0.83, 0 ≤ z6 ≤ 0.83, M6 includes at least one of Ta, Zr, Ca, and Al, and Ln includes at least one of La, Ce, Pr, Nd, and Sm; LiM7Cl5X5 satisfies: M7 includes at least one of La, Ta, and Nb, and X5 includes at least one of O, Cl, F, and OH; Li 3-y7 Zr y7 M8 1-y7 Cl6 satisfies: 0 < y7 < 1, and M8 includes at least one of Y, Er, Yb, Ho, and Lu.
[0084] As an example, the hydride solid electrolyte includes at least one of Li3AlH6, LiBH4, LiNH2, Li2NH, LiBH4 - LiNH2, LiBH4 - LiX6, where LiBH4 - LiX6 satisfies: X includes at least one of Cl, Br, and I.
[0085] As an example, the borate solid electrolyte can be selected from at least one of Li2B4O7 and Li2O - B2O3 - P2O5.
[0086] As an example, the nitride solid electrolyte can be selected from at least one of LiPON, Li3N, Li7PN4, and LiSi2N3.
[0087] As an example, the polymer solid electrolyte includes a lithium salt and a polymer.
[0088] As an example, the polymer includes but is not limited to one or more of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluorochloroethylene, polyacrylonitrile, polymethyl methacrylate, polypropylene carbonate, polyphenylene sulfide, polyethyl cyanoacrylate, polypentylene succinate, polyvinyl chloride, polyvinylene carbonate, chitosan, polyimide, polyacrylate, polyurethane, polyetherimide, polyamide, polysulfone, aromatic sulfone, polyaromatic sulfone, polyether sulfone, epoxy resin and polyphenylene sulfone resin.
[0089] According to some embodiments of the present invention, the lithium-philic active layer 2 also includes a binder and an active additive. The binder can make the lithium-philic active layer 2 firmly attached to the current collector 1 without falling off, thereby improving the stability of the negative electrode plate 10 and improving the cycle performance of the battery; the active additive works together with the nanowires 21 dispersed with conductive particles 22 to further form a stable SEI at the interface, thereby improving the orderly deposition of the lithium metal lithium-philic active layer 2, thereby improving the cycle performance and coulombic efficiency of the battery.
[0090] According to some embodiments of the present invention, based on the total mass of the lithium-philic active layer 2, the mass proportion of the binder is less than or equal to 3%, for example, it can be 0.1%, 0.5%, 1%, 2%, 2.9%, etc., and the content of the binder is controlled within the above range, which can ensure that the lithium-philic active layer 2 does not fall off from the current collector 1, and does not cause excessive binder to affect lithium deposition, thereby further improving the cycle performance and coulombic efficiency of the battery.
[0091] It should be noted that there is no particular limitation on the type of binder, and those skilled in the art can flexibly select the binder as needed.
[0092] As an example, the binder includes at least one of polyvinylidene fluoride, polyvinyl alcohol, polytetrafluoroethylene, sodium hydroxymethyl cellulose, styrene-butadiene rubber, nitrile rubber, styrene-butadiene-styrene copolymer, polyacrylic acid, and lithium polyacrylate.
[0093] According to some embodiments of the present invention, based on the total mass of the lithium-philic active layer 2, the mass proportion of the active additive is 0.1%-10%, for example, it can be 0.1%, 1%, 3%, 5%, 7%, 10%, etc., and controlling the content of the active additive within the above range is more conducive to its interaction with the nanowires 21 dispersed with conductive particles 22, further forming a stable SEI at the interface, improving the orderly deposition of the lithium metal re-lithiophilic active layer 2, and thereby improving the cycle performance and coulombic efficiency of the battery.
[0094] According to some embodiments of the present invention, the active additive includes at least one of lithium nitrate, lithium fluoride, and lithium nitride. The above active additive can work together with the nanowires 21 dispersed with conductive particles 22 to further form a stable SEI at the interface, improve the orderly deposition of the lithium metal re-lithiophilic active layer 2, and thus improve the cycle performance and rate performance of the battery.
[0095] In a second aspect, the present invention provides a method for preparing the negative electrode sheet 10 of the first aspect. According to an embodiment of the present application, the method comprises:
[0096] A lithium-philic active layer 2 is prepared on at least one side of the current collector 1 , wherein the lithium-philic active layer 2 includes nanowires 21 and conductive particles 22 dispersed on the nanowires 21 . When lithium metal is deposited, the nanowires 21 provide nucleation sites for the lithium metal.
[0097] According to the method of the embodiment of the present application, the negative electrode sheet 10 is prepared, the current collector 1 is used as the basic support, and the lithium-philic active layer 2 is arranged on at least one side of the current collector 1. When the battery is charged, the nanowires 21 provide nucleation sites for lithium metal, which can be used as the substrate of the lithium-philic active layer 2, provide a homogeneous high-speed channel, and provide a monodisperse active attachment site for the composite of the conductive particles 22, solving the problems of low specific surface area of single active site particles and easy agglomeration, and the one-dimensional nanowires 21 can further reduce the contact area with the battery electrolyte, reduce the side reactions of the system, and improve the cycle performance of the battery containing it; the integrated composite negative electrode composed of silver nanowires and conductive particles 22 can simultaneously achieve atomic level The stable transmission channels in the bulk and interface are eliminated from the source, which causes the disordered growth of lithium dendrites caused by the uneven dispersion of nanowires 21 and conductive particles 22, and improves the cycle performance and coulombic efficiency of the battery. In addition, the contact position between the conductive particles 22 and the nanowires 21 is constructed as a homogeneous interface and a highly active lithium conductive site, which can effectively increase the content of effective active sites per unit area, improve the cycle performance and coulombic efficiency of the battery, and can also reduce the amount of raw materials used and reduce the cost of battery use. In summary, the negative electrode plate 10 proposed in the present application is conducive to the uniform deposition of lithium metal during the battery charging process, and can reduce lithium dendrites, thereby improving the cycle performance and rate performance of the battery.
[0098] According to some embodiments of the present invention, the lithium-philic active layer 2 is prepared by the following method:
[0099] The nanowires 21 dispersed with the conductive particles 22 , a binder and an active additive are dispersed in an organic solvent to obtain a slurry, which is then coated on the current collector 1 and dried to obtain the negative electrode sheet 10 .
[0100] It is understood that the nanowires 21 dispersed with the conductive particles 22 can be prepared by conventional methods in the art, for example:
[0101] Dispersing the conductive particles 22 (and optional blends) in a first solvent to form a first suspension;
[0102] Dispersing the nanowires 21 in a second solvent to prepare a second suspension;
[0103] The first suspension and the second suspension are mixed and dried to obtain nanowires 21 dispersed with conductive particles 22 .
[0104] Specifically, taking the conductive particles 22 as conductive carbon black and the nanowires 21 as silver nanowires as an example, the preparation method is as follows:
[0105] 1. Conductive carbon black dispersion: firstly, conductive carbon black is added to an appropriate amount of solvent, and ultrasonic stirring is performed to disperse the conductive carbon black, and then the blend is added to the blend to obtain a first suspension for standby after ultrasonic dispersion;
[0106] 2. Preparation of silver nanowires: adding ammonia water to a silver nitrate solution to obtain a silver ammonia solution, adding a surfactant, adding a reducing agent to the solution, adding a functional group precursor, heating and stirring to reduce, obtaining a second suspension, and the solvent of the silver nitrate solution is the second solvent; (you can also directly purchase silver nanowires and disperse them in the second solvent)
[0107] 3. The first suspension is dropped into the second suspension, and after being fully mixed by ultrasonication, the mixed solution is washed, centrifuged, dried and ground to obtain nanowires 21 dispersed with conductive particles 22.
[0108] According to some embodiments of the present invention, the first solvent and the second solvent each independently include at least one of deionized water, ammonia water, toluene, xylene, trimethylbenzene, cyclohexane, n-hexane, ethanol, acetone, chloroform, acetonitrile, ethylene glycol, pentylene glycol, ethylene glycol dimethyl ether, oleic acid, octadecene, ethylenediamine, triethylamine, diphenyl ether, diphenyl ether, dimethylformamide, diethyltoluenediamine, dimethyl sulfoxide, diacetone alcohol, nitrogenmethylpyrrolidone, dimethylformamidetrichloromethane, ethyl acetate, N,N dimethylformamide, N,N dimethylacetamide, pyridine and tetrahydrofuran.
[0109] According to some embodiments of the present invention, the organic solvent includes but is not limited to N,N-dimethylformamide.
[0110] According to some embodiments of the present invention, the nanowire 21 comprises a silver nanowire, a functional group is grafted onto the silver nanowire, and the functional group comprises at least one of a silicon-containing functional group, a nitrogen-containing functional group, a sulfur-containing functional group and a boron-containing functional group, and the silver nanowire is prepared by the following method:
[0111] A silver nanowire precursor, a functional group precursor, a reducing agent, a surfactant and a solvent are mixed and subjected to a reduction reaction to obtain silver nanowires grafted with functional groups.
[0112] Functional groups are grafted onto silver nanowires, and at least one of silicon-containing functional groups, nitrogen-containing functional groups, sulfur-containing functional groups and boron-containing functional groups can be stably grafted onto lithium-philic active sites. The grafting of functional groups can effectively prevent the agglomeration of lithium-philic active sites, ensure that the lithium-philic active sites can be evenly distributed on the current collector 1 in a dispersed state, and then induce the lithium metal to be evenly dispersed on the current collector 1; the grafting of functional groups can also firmly anchor the lithium-philic active sites on the surface of the current collector 1, prevent the lithium-philic active sites from falling off or moving during the battery cycle, which is beneficial to maintaining the battery's cycle stability; the lithium-philic active sites grafted with functional groups can form lithium metal nucleation sites, induce lithium ions to be directional deposited along the (110) crystal plane, thereby inhibiting the disordered growth of lithium dendrites, which is beneficial to improving the safety performance and cycle stability of lithium batteries.
[0113] According to some embodiments of the present invention, the functional group precursor includes at least one of dopamine, silicon fluoride, aromatic amine, sulfonylated amine, halogenated aromatic amine, nitrogen-containing heterocyclic compound, nitrile compound, nitro compound, thiophene-containing compound, furanyl thiocarboxylate and thiourea. The above functional group precursor can provide at least one of silicon-containing functional group, nitrogen-containing functional group, sulfur-containing functional group and boron-containing functional group, ensuring that the lithium-philic active sites can be evenly distributed on the current collector 1 in a dispersed state, inhibiting the disordered growth of lithium dendrites, which is beneficial to improving the safety performance and cycle stability of lithium batteries.
[0114] According to some embodiments of the present invention, the temperature of the reduction reaction is 60°C-180°C, for example, it can be 60°C, 80°C, 100°C, 130°C, 150°C, 180°C, etc. By controlling the temperature of the reduction reaction within the above range, the inability to form nanowires 21 caused by too low temperature can be reduced, and the agglomeration of nanowires 21 caused by too high temperature can be reduced, so as to form uniform nanowires 21 with better morphology, facilitate the deposition of lithium metal, and facilitate the uniform deposition of conductive particles 22 thereon, reduce the agglomeration of nanowires 21 and conductive particles 22, further improve the lithium conductivity and electrical conductivity of the lithium-philic active layer 2, reduce the generation of lithium dendrites, and improve the coulombic efficiency and cycle stability of the lithium battery.
[0115] As an example, the silver nanowire precursor includes a silver ammonia solution, and the silver ammonia solution includes a silver salt and ammonia water.
[0116] As an example, the silver nanowire precursor includes a silver salt, and the silver salt includes at least one of silver nitrate, silver bromide, silver sulfate, silver fluoride, silver perchlorate, and silver acetate.
[0117] As examples, the reducing agent includes ascorbic acid, zinc powder, glucose, hydrazine hydrate, dodecyltetraethylene glycol ether, dimethylamine-borane, and sodium citrate.
[0118] According to some embodiments of the present invention, the surfactant includes at least one of cupric chloride, cuprous chloride, sodium chloride, cupric bromide, cuprous bromide, ferric chloride, ferrous chloride, ferric bromide, ferrous bromide, trioctyl phosphine, trioctyl phosphine oxide, long-chain alkyl salts, polyvinyl pyrrolidone, oleylamine, polyethylene glycol, Tween, triethanolamine, hexadecyltrimethylammonium bromide, polyacrylamide, di-(2-ethylhexyl) sodium sulfosuccinate, sodium dodecyl sulfate, lithium dodecyl sulfate, dodecyldimethylammonium chloride, dodecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride, dodecyldimethylammonium oxide, dodecyl betaine, hexadecyltrimethylammonium chloride, and amidopropyl betaine. The above-mentioned surfactant can form uniform nanowires 21 with good morphology, facilitate the deposition of lithium metal, and facilitate the uniform deposition of conductive particles 22 thereon, reduce the agglomeration of nanowires 21 and conductive particles 22, further improve the lithium conductivity and electrical conductivity of the lithium-philic active layer 2, reduce the generation of lithium dendrites, and can improve the coulombic efficiency and cycle stability of lithium batteries.
[0119] In a third aspect of the present invention, the present invention provides a negative electrode-free lithium battery. According to an embodiment of the present invention, the negative electrode-free lithium battery comprises the negative electrode plate of the first aspect or the negative electrode plate prepared by the method of the second aspect. The negative electrode-free lithium battery has excellent cycle performance and coulombic efficiency.
[0120] It should be noted that the features and advantages described above for the negative electrode plate and its preparation method are also applicable to the battery and will not be repeated here.
[0121] It can be understood that a battery without negative electrode means that no negative electrode active material lithium metal is added during the battery preparation stage, but there is still a negative electrode current collector. A battery without negative electrode is just a special lithium metal battery. It does not really have no negative electrode. The negative electrode in the actual working process still has lithium metal. + It is extracted from the positive electrode and deposited on the negative electrode current collector to form a lithium negative electrode. During the discharge process of the battery, the deposited lithium metal dissolves and is embedded back into the positive electrode again.
[0122] In a fourth aspect of the present invention, the present invention provides a lithium battery. According to an embodiment of the present invention, the lithium battery comprises the negative electrode sheet of the first aspect or the negative electrode sheet prepared by the method of the second aspect. The lithium battery has excellent cycle performance and coulombic efficiency.
[0123] It should be noted that the features and advantages described above for the negative electrode plate and its preparation method are also applicable to the battery and will not be repeated here.
[0124] It should be noted that the lithium battery and the negative electrode-free lithium battery also include a positive electrode plate, the positive electrode plate includes a current collector and a positive electrode active material layer, the positive electrode active material layer is arranged on at least one side of the current collector, the positive electrode active material layer includes but is not limited to a positive electrode active material, a conductive agent and a binder, the positive electrode active material includes but is not limited to lithium cobalt oxide, lithium nickel oxide, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, lithium-rich manganese base, lithium manganese oxide, lithium nickel manganese oxide, ferroferric oxide and lithium vanadate, lithium iron phosphate, lithium manganese phosphate, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium nickel phosphate, lithium iron silicate, lithium ferrous sulfate, lithium iron borate and lithium iron titanate, the conductive agent includes but is not limited to at least one of carbon black and graphite, and the binder includes but is not limited to polyvinylidene fluoride (PVDF) and the like.
[0125] In some embodiments of the present invention, the positive electrode sheet can be prepared by the following method:
[0126] The components used to prepare the positive electrode plate, such as the positive electrode active material, the conductive agent, the binder, the ionic liquid-based liquid crystal and any other components are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode plate can be obtained.
[0127] In some embodiments of the present invention, the solvent includes at least one of diethyl ether, ethanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid and sebacononitrile.
[0128] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.
[0129] Example 1
[0130] 1. Preparation of negative electrode sheet:
[0131] (1) Dispersing conductive carbon black: firstly, adding conductive carbon black into an appropriate amount of deionized water, dispersing by ultrasonic stirring, and then adding the blended polyaniline and dispersing by ultrasonic stirring to obtain a first suspension for use;
[0132] (2) Preparation of silver nanowires: adding ammonia water to an aqueous solution of silver nitrate to obtain a silver ammonia solution, adding a surfactant, triethanolamine, and adding a reducing agent (ascorbic acid) to the solution, adding a functional group precursor, dopamine, heating at 80° C. and stirring for reduction to obtain a second suspension, and obtaining silver nanowires with a length of 10 μm and a diameter of 50 nm;
[0133] (3) dropping the first suspension into the second suspension, mixing thoroughly with ultrasound, washing, centrifuging, drying and grinding the mixed solution to obtain nanowires dispersed with conductive carbon black;
[0134] (4) preparing an aqueous solution of a binder, then adding nanowires dispersed with conductive carbon black to the binder solution to prepare a negative electrode slurry, and adding an active additive, wherein the mass ratio of the nanowires dispersed with conductive carbon black, the active additive and the binder is 93:5:2, and finally coating the slurry on a stainless steel current collector, and vacuum drying to obtain a negative electrode sheet containing a lithium-philic active layer, wherein the thickness of the lithium-philic active layer is 100 μm and the compaction density is 1.2 g / cm 3 .
[0135] 2. Preparation of solid electrolyte:
[0136] LLZO(Li7La3Zr2O 12 ), PVDF, and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide) are dispersed in DMF in a ratio of 6:3:1, and then introduced onto the prepared negative electrode sheet by ultrasonic spraying. After drying, the solid electrolyte layer is rolled to form a solid electrolyte layer with a thickness of 10μm.
[0137] 3. Prepare the positive electrode sheet: dissolve the positive electrode active material NCM811, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride in N-methylpyrrolidone, with the mass ratio of positive electrode active material: conductive agent: binder being 96:2:2, and then apply it on the surface of the current collector, dry it, and roll it to obtain the positive electrode sheet.
[0138] 4. Prepare lithium battery: Assemble the negative electrode sheet and positive electrode sheet obtained above into a battery, and integrate them by hot pressing to obtain a negative electrode-free lithium battery.
[0139] The negative electrode sheets of Examples 2-23 and the comparative examples are the same as Example 1 except for the different experimental parameters (see Table 1). Among them, compared with the preparation method of Example 1, the parameters changed in Example 2 are the type of silver salt is silver fluoride, the temperature is 80°C and the reducing agent is hydrazine hydrate, compared with the preparation method of Example 1, the parameters changed in Example 3 are the reducing agent hydrazine hydrate and the temperature is 95°C, compared with the preparation method of Example 1, the parameters changed in Example 4 are the temperature of 130°C, compared with the preparation method of Example 1, the parameters changed in Example 5 are the temperature of 150°C, compared with the preparation method of Example 1, the parameters changed in Example 6 are the reducing agent is glucose, the temperature is 80°C and the reaction time is 2h, compared with the preparation method of Example 1, the parameters changed in Example 7 are the reducing agent glucose, the temperature is 90°C and the reaction time is 3h, compared with the preparation method of Example 1, the parameters changed in Example 8 are the temperature of 90°C and the reaction time is 6h, compared with the preparation method of Example 1, the parameters changed in Example 9 are the temperature of The temperature is 90°C and the reaction time is 12h. Compared with the preparation method of Example 1, the changed parameters of Example 10 are the reducing agent glucose, the temperature is 85°C and the reaction time is 4h. Compared with the preparation method of Example 1, the changed parameters of Example 11 are the type of silver salt is silver fluoride, the temperature is 85°C and the reaction time is 5h. Compared with the preparation method of Example 12, the changed parameters are the type of silver salt is silver fluoride, the temperature is 85°C and the reaction time is 6h. Compared with the preparation method of Example 1, the changed parameters of Example 13 are the type of nanowires is silicon nanowires. The silver nanowires of Example 23 are not grafted with functional groups. Compared with Example 1, the functional group precursor dopamine is not added in step (2). Comparative Example 1 is silver nanowire particles with a Dv50 particle size of 50nm. Comparative Example 2 does not contain silver nanowires in the lithium-philic active layer. Comparative Example 3 does not contain conductive particles in the lithium-philic active layer.
[0140] Some experimental parameters of the negative electrode sheets of Examples 1-23 and the comparative example are shown in Table 1.
[0141] Table 1
[0142]
[0143]
[0144] Testing and analysis
[0145] Under the same conditions, the lithium batteries prepared in the above Examples 1-23 and the comparative example were subjected to rate performance, cycle performance and safety performance tests. The specific test methods are as follows:
[0146] Coulomb efficiency test: Assemble button cells at 25°C, charge and discharge at 0.1C rate, record the charge and discharge capacity, and calculate the coulomb efficiency of the button cell.
[0147] Cycle capacity retention rate test: In a glove box containing argon, the positive and negative battery shells, stainless steel gaskets, spring sheets, positive electrode sheets, and negative electrode sheets are assembled into button cells. After the button cells are assembled, they are left to stand at 25°C for 6 hours, and then the constant current charge and discharge mode test is performed using a charge and discharge instrument model CT2001A purchased from Wuhan Blue Electric Electronics Co., Ltd. - the battery is first charged, and the battery charge cutoff voltage is 4.2V, and then discharged, and the discharge cutoff voltage is 2.75V, and the test temperature is 25°C. The battery charge and discharge test first performs 2 cycles of activation at a rate of 0.1C, and then performs a long cycle at a rate of 0.5C.
[0148] The test results are shown in Table 2.
[0149] Table 2
[0150]
[0151]
[0152] “ / ” indicates poor performance and data cannot be measured.
[0153] Combining Table 1 and Table 2, it can be obtained that compared with the lithium battery of Comparative Examples 1-3, the lithium battery of Example 1-23, by setting nanowires and conductive particles dispersed thereon in the lithium-philic active layer, when lithium metal is deposited, the nanowires provide nucleation sites for lithium metal, which is conducive to the uniform deposition of lithium metal during battery charging, and can reduce lithium dendrites, improve the cycle performance and coulomb efficiency of the battery. Compared with Examples 1-24, Comparative Example 1 replaces silver nanowires with silver nanoparticles, Comparative Example 2 does not use silver nanowires, and Comparative Example 3 does not contain conductive particles. The performance of the battery is significantly lower than that of Examples 1-24. It can be seen that the embodiments of the present application can significantly improve the cycle performance and coulomb efficiency of lithium batteries.
[0154] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0155] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A negative electrode plate, characterized in that: include: current collector; The lithium-philic active layer is disposed on at least one side of the current collector. The lithium-philic active layer includes nanowires and conductive particles dispersed on the nanowires. When lithium metal is deposited, the nanowires provide nucleation sites for the lithium metal.
2. The negative electrode sheet according to claim 1, characterized in that: The diameter of the nanowire is 1nm-100nm, preferably 2nm-100nm; Preferably, the length of the nanowire is 1 μm-100 μm, preferably 1 μm-80 μm; Preferably, the nanowire comprises a first nanowire and a second nanowire, the first nanowire has a length of 10 μm-100 μm, and the second nanowire has a length of 1 μm-20 μm; Preferably, the Dv50 particle size of the conductive particles is 0.5nm-100nm; Preferably, the compaction density of the lithium-philic active layer is 0.3 g / cm 3 -2.0g / cm 3 .
3. The negative electrode sheet according to claim 1, characterized in that: The mass ratio of the nanowires to the conductive particles is (1:9)-(9:1).
4. The negative electrode sheet according to claim 1, characterized in that: The nanowires include at least one of silver nanowires, magnesium nanowires, zinc nanowires, nickel nanowires, aluminum nanowires, gold nanowires, molybdenum nanowires, lead nanowires, tin nanowires, bismuth nanowires, palladium nanowires, ruthenium nanowires, iridium nanowires, platinum nanowires, cerium nanowires, indium nanowires, silicon nanowires, and oxide nanowires, sulfide nanowires, and solid electrolyte nanowires; Preferably, the conductive particles include at least one of one-dimensional conductive particles, two-dimensional conductive particles, and three-dimensional conductive particles; Preferably, the conductive particles include at least one of carbon quantum dots, fullerenes, conductive carbon black, conductive graphite, acetylene black, Ketjen black, carbon fibers, carbon nanotubes, graphene, silicon carbide, boron carbide, silicon boride, vanadium boride, magnesium boride, and titanium boride.
5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The nanowire is grafted with a functional group, and the functional group includes at least one of a silicon-containing functional group, a nitrogen-containing functional group, a sulfur-containing functional group, and a boron-containing functional group; Preferably, the conductive particles further include a blend, wherein the blend includes at least one of a solid electrolyte and a conductive polymer; Preferably, the thickness of the lithium-philic active layer is 10 μm-200 μm, preferably 30 μm-120 μm.
6. The negative electrode sheet according to claim 5, characterized in that: The mass of the functional group accounts for 0.1%-3% of the mass of the nanowire; Preferably, based on the total mass of the conductive particles, the mass proportion of the blend is 0.1%-10%; Preferably, the conductive polymer comprises a nitrogen-containing polymer; Preferably, the conductive polymer includes at least one of polyaniline, polythiophene, polypyrrole, polyphenylene sulfone resin, polyurethane, polyamide, 6-amino-1-hexanol-polyacrylic acid ion cross-linked polymer, hydroxyethylethylenediamine-polyacrylic acid ion cross-linked polymer, diglycolamine-polyacrylic acid ion cross-linked polymer, 5-amino-1-pentanol-polyacrylic acid ion cross-linked polymer, 4-amino-1-butanol-polyacrylic acid ion cross-linked polymer, and N,N-bis(2-hydroxyethyl)ethylenediamine-polyacrylic acid ion cross-linked polymer.
7. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The lithium-philic active layer also includes a binder and an active additive; Preferably, based on the total mass of the lithium-philic active layer, the mass proportion of the binder is less than or equal to 3%; Preferably, based on the total mass of the lithium-philic active layer, the mass proportion of the active additive is 0.1%-10%; Preferably, the binder includes at least one of polyvinylidene fluoride, polyvinyl alcohol, polytetrafluoroethylene, sodium hydroxymethyl cellulose, styrene-butadiene rubber, nitrile rubber, styrene-butadiene-styrene copolymer, polyacrylic acid, and lithium polyacrylate; Preferably, the active additive includes at least one of lithium nitrate, lithium fluoride and lithium nitride.
8. A method for preparing the negative electrode sheet according to any one of claims 1 to 7, characterized in that: The method comprises: A lithium-philic active layer is prepared on at least one side of a current collector. The lithium-philic active layer includes nanowires and conductive particles dispersed on the nanowires. When lithium metal is deposited, the nanowires provide nucleation sites for the lithium metal.
9. The method according to claim 8, characterized in that The lithium-philic active layer is prepared by the following method: The nanowires dispersed with conductive particles, a binder and an active additive are dispersed in an organic solvent to obtain a slurry, the slurry is coated on a current collector, and dried to obtain a negative electrode sheet.
10. The method according to claim 8, characterized in that The nanowires include silver nanowires, functional groups are grafted onto the silver nanowires, and the functional groups include at least one of silicon-containing functional groups, nitrogen-containing functional groups, sulfur-containing functional groups, and boron-containing functional groups. The silver nanowires are prepared by the following method: A silver nanowire precursor, a functional group precursor, a reducing agent, a surfactant and a solvent are mixed and subjected to a reduction reaction to obtain silver nanowires grafted with functional groups.
11. The method according to claim 10, characterized in that The functional group precursor includes at least one of dopamine, silicon fluoride, aromatic amine, sulfonylated amine, halogenated aromatic amine, nitrogen-containing heterocyclic compound, nitrile compound, nitro compound, thienyl-containing compound, furanyl thiocarboxylate and thiourea; Preferably, the temperature of the reduction reaction is 60°C-180°C; Preferably, the silver nanowire precursor comprises a silver salt, and the silver salt comprises at least one of silver nitrate, silver bromide, silver sulfate, silver fluoride, silver perchlorate, and silver acetate; Preferably, the surfactant includes at least one of cupric chloride, cuprous chloride, sodium chloride, cupric bromide, cuprous bromide, ferric chloride, ferrous chloride, ferric bromide, ferrous bromide, trioctyl phosphine, trioctyl phosphine oxide, long-chain alkyl salts, polyvinyl pyrrolidone, oleylamine, polyethylene glycol, Tween, triethanolamine, hexadecyltrimethylammonium bromide, polyacrylamide, di-(2-ethylhexyl) sodium sulfosuccinate, sodium dodecyl sulfate, lithium dodecyl sulfate, dodecyldimethylammonium chloride, dodecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride, dodecyldimethylammonium oxide, dodecyl betaine, hexadecyltrimethylammonium chloride, and amidopropyl betaine.
12. The method according to claim 8, characterized in that The nanowires dispersed with conductive particles are prepared by the following method: Dispersing conductive particles in a first solvent to form a first suspension; dispersing the nanowires in a second solvent to prepare a second suspension; The first suspension and the second suspension are mixed and dried to obtain nanowires dispersed with conductive particles.
13. A negative electrode-free lithium battery, characterized in that: The negative electrode-free lithium battery comprises the negative electrode plate according to any one of claims 1 to 7 or the negative electrode plate prepared by the method according to any one of claims 8 to 12.
14. A lithium battery, characterized in that: The lithium battery comprises the negative electrode sheet according to any one of claims 1 to 7 or the negative electrode sheet prepared by the method according to any one of claims 8 to 12.
Citation Information
Patent Citations
Low-internal resistance lithium ion battery and preparation method thereof
CN104577117A
Conducting Polymer Network-Protected Nanowires of an Anode Active Material for Lithium-Ion Batteries
US20210280871A1
Cited By
Preparation method and application of carbon-coated silicon nanowire negative electrode material
CN120809756A
Preparation method and application of carbon-coated silicon nanowire negative electrode material
CN120809756B
Modified current collector, preparation method and negative-electrode-free sodium metal battery
CN121097087A
Negative electrode composite current collector of non-negative electrode lithium battery and preparation method of negative electrode composite current collector
CN121709629A
Hybrid polymer modified current collector, preparation method thereof and battery
CN121812607A